STUDI HOLISTIK PERBEDAAN KONSEP MANUSIA DALAM PSIKOLOGI BARAT DAN PSIKOLOGI ISLAM - Maruf, Muhammad; Subaidi (Kodifikasia, 2024)
This article analyzes the differences and integration of human concepts in Western psychology and Islamic psychology. This study uses a library research method by collecting data, analyzing data, and concluding the analysis of the text. This approach was chosen because it allows researchers to explore and compare various theories, views, and existing research without being limited by time and geographical space. This study produces an analysis that Western Psychology, which developed from classical Greek philosophical thought to modern theories, emphasizes an empirical and scientific approach in understanding human behavior. In contrast, Islamic psychology offers a holistic perspective that combines spiritual, moral, and psychological aspects. This study aims to understand the fundamental differences in the two approaches and explore the possibility of integration to develop more inclusive and effective psychological interventions.